Isaak - Deocampo, Nick. ([Honolulu, Hawaii] Asia Pacific Films, 1996)
Based on a painting by Rembrandt, "The Sacrifice of Isaac," the film is a meditation on the complex relations between fathers and sons. In two parallel stories, a son's desire to be free is shown as he struggles from his father's oppressive domination. This is shown on the one hand by a boy who watches over his father in his sickbed wishing to free himself from his father's domineering presence; and on the other, a biblical Isaac who frees himself from Abraham's intent to kill his own son.
Library has: VDR-1667 (1 DVD)
Cast, Chris Isaak, Tony Mabesa.
DVD
Keywords: Homosexuality -- Philippines; Father and sons; Families -- Philippines; Gender identity -- Philippines